Understanding the benefits of product-service system for involved parties in remanufacturing - Anjar Priyono (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: This study aims to analyse the benefit provided by interested parties in remanufacturing including manufacturing companies, original equipment manufacturers and customers. Existing studies examining Produc-Service System (PSS) focus on relationship between two parties, either between OEMs and customers or between remanufacturers with customers. This study attempts to fill the gap by investigating how the PSS offers benefit to OEMs, remanufacturers and customers. Methodology: This research used case study method to examine the practice of PSS in remanufacturing companies. Qualitative approach was employed to analyse emerging problems in the case companies and the researcher collaborate with the involved parties to create new knowledge. Thus, this process can offer theoretical insights as well as practical insights. Findings: All parties involved in PSS consistently gain benefit from adopting the practice. From the perspective of remanufacturers, the major benefit of remanufacturers adopting PSS is that it can help reduce the uncertainties regarding time, quantity and quality of returned cores. Due to reduced uncertainties, remanufacturers gain benefit from higher profitability and more environmental friendly products. These benefits provide multiplier effects to both customers and OEMs. Practical implications: This study offers benefits to managers in the sense that it provides guidance for managers of remanufacturers to better manage remanufacturing operation so that it becomes more environmentally friendly and economically profitable. Originality/value: It is the first time that the benefits of PSS to support remanufacturing are viewed from integrative perspective - i.e. manufacturers, remanufacturers, and customers.
Keywords: 650; remanufacture; product service system; sustainability; operations management; environmental issues; reverse logistics